Effect of ethnicity, gender and drug use history on achieving high rates of affirmative informed consent for genetics research: impact of sharing with a national repository. Issue 6 (25th January 2011) - Ray, Brenda; Jackson, Colin; Ducat, Elizabeth; Ho, Ann; Hamon, Sara; Kreek, Mary Jeanne
Abstract : Aim: Genetic research representative of the population is crucial to understanding the underlying causes of many diseases. In a prospective evaluation of informed consent we assessed the willingness of individuals of different ethnicities, gender and drug dependence history to participate in genetic studies in which their genetic sample could be shared with a repository at the National Institutes of Health. Methods: Potential subjects were recruited from the general population through the use of flyers and referrals from previous participants and clinicians with knowledge of our study. They could consent to 11 separate choices so that they could specify how and with whom their genetic sample could be shared. Rates of affirmative consent were then analysed by gender, ethnicity and drug dependence history. Results: Of 1416 volunteers enrolled, 99.7% gave affirmative informed consent for studies of addiction conducted in our laboratory. No significant difference was found for participation in genetic studies conducted in our laboratory by gender, ethnicity or drug dependence history. Over all 11 questions, individuals with a history of drug use were more likely to agree to consent to participate in our study than were healthy volunteers. Conclusion: A high percentage of each category of gender, ethnicity and drug history, gave affirmative consent at all levels. The level of detail in and the amount of time spent reviewing the informed consent, and a relationship of trust with the clinical investigator may contribute to this outcome.